Anaerobic codigestion of pretreated wheat straw with cattle manure and analysis of the microbial community. (June 2015) - Song, Zilin; Zhang, Chao
Highlights: Wheat straw (WS) pretreated with H2 O2 was codigested with cattle manure (CM). Methanogenic community was measured by the high-throughput sequencing technique. The optimal concentration of H2 O2 for treating WS was 3%. A 40:60 ratio of H2 O2 -treated WS mixed with CM produced the highest methane yield. Methanogen shifted from acetoclastic to hydrogenotrophic population in digestion. Abstract: Wheat straw (WS) was pretreated with four concentrations of H2 O2 (1%, 2%, 3%, and 4%) and was anaerobically codigested with dairy cattle manure (CM) at various ratios from 100:0 to 0:100. Wet-state H2 O2 pretreatment effectively enhanced the biodegradability and methane yield of the WS. The optimal concentration of H2 O2 for treating WS was 3%. The methane yield was higher with the codigestion of CM and H2 O2 -treated WS than with untreated WS and higher than with H2 O2 -treated WS alone or CM alone. A 40:60 ratio of H2 O2 -treated WS mixed with CM produced the highest yield of methane (320.8 mL g volatile solid (VS) −1 ). Results of high-throughput sequencing indicated that the methanogenic community shifted during the codigestion from the acetoclastic methanogens, Methanosarcina, to the hydrogenotrophic methanogens, Methanosphaera and Methanoculleus .